Feasibility of certified quality management in a comprehensive stroke care network using telemedicine: STENO project. Issue 8 (4th August 2014) - Handschu, René; Scibor, Mateusz; Wacker, Angela; Stark, David R.; Köhrmann, Martin; Erbguth, Frank; Oschmann, Patrick; Schwab, Stefan; Marquardt, Lars
Abstract : Background: Stroke care networks with and without telemedicine have been established in several countries over the last decade to provide specialized stroke expertise to patients in rural areas. Acute consultation is a first step in the management of stroke, but not the only one. Methods of standardization of care and treatment are much needed. So far, quality management systems have only been used for single stroke units. To the best of our knowledge, we are the first stroke network worldwide to aim for certification of a network‐wide quality management system. Methods: The Stroke Network Using Telemedicine in Northern Bavaria (STENO), currently with 20 associated medical institutions, is one of the world's largest stroke networks, caring for over 5000 stroke patients each year. In 2010, we initiated the implementation of a network‐wide 'total' quality management system according to ISO standard 9001:2008 in cooperation with the German Stroke Society and a third‐party certification organization (LGA InterCert). Results: Certification according to ISO 9001:2008 was awarded in March 2011 and maintained over a complete certification cycle of 3 years without major deviation from the norm in three external third‐party audits. Thrombolysis rate significantly increased from 8·2% (2009) to 12·8% (2012). Conclusions: Certified quality management within a large stroke network using telemedicine is possible and might improve stroke care procedures and thrombolysis rates. Outcome studies comparing conventional stroke care and telestroke care are inevitable.